2022
DOI: 10.1021/acsami.1c21441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanoparticle Size on Plasmon-Driven Reaction Efficiency

Abstract: Hot electron chemistry is of paramount significance because of its applicability to photocatalytic reactions, solar energy conversion, and waste decomposition. The nonradiative decay of excited plasmons in gold nanoparticles (AuNPs) generates highly energetic nonthermal electrons and holes that can induce chemical reactions when transferred to nearby molecules. In this study, we explore the relationship between AuNP size (26−133 nm) and the plasmoninduced reaction yield. To isolate the size from other structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 45 publications
2
38
1
Order By: Relevance
“…For this, the optical density (0.4) at the surface plasmon band of each AuNPs was normalized for a fair comparison of the size effect, which is a commonly used normalization strategy. [11] The broad emission peak of LEDs (� 40 nm) will take care of the difference in the λ max position of different sizes of AuNPs. The time of irradiation was reduced to 75 min in order to accommodate for the higher yield that may be obtained with different sizes of AuNPs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this, the optical density (0.4) at the surface plasmon band of each AuNPs was normalized for a fair comparison of the size effect, which is a commonly used normalization strategy. [11] The broad emission peak of LEDs (� 40 nm) will take care of the difference in the λ max position of different sizes of AuNPs. The time of irradiation was reduced to 75 min in order to accommodate for the higher yield that may be obtained with different sizes of AuNPs.…”
Section: Resultsmentioning
confidence: 99%
“…This essentially means that the scattering cross-section will keep on increasing as a function of NP size; whereas the absorption cross-section will reach a plateau at a particular size regime. [11] Likewise, the heat dissipation step is related to the size of the AuNPs. It has been shown that the rate of heat dissipation decreases with an increase in NP size, because of the higher heat capacity for larger NPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] Fang and co-workers previously examined the emission effect of photoexcited hot electrons from plasmonic metal nanostructure, which is still a challenging issue in the field of nanophotonics for solar harvesting, water splitting, photocatalysis, and a variety of optical sensing. [12] In this work, the investigation of spaced CVD-GM in NPoM for the locational relationship by loading individual Au nanoparticles (NPs) likewise seminanoindentation through the AFM topography with corresponding Raman image (and SERS spectral behaviors) is carried out and discovered the domain-dependent (the most outer/center domain) different defect types phenomena in the NPoM system [13][14][15][16][17][18][19][20][21][22][23][24] in terms of establishing the new defect domain-selective sensing platform. The individual NPoM plasmonic junction, composed of Au NP/CVD-GM /Au TF, can be precisely inspected by AFM, and the author can find out that the line profile of the most outer domain of NPoM shows near-two symmetrical deep pits, due to probably physical loading of Au NP onto the CVD-GM/Au TF.…”
mentioning
confidence: 99%